2000
DOI: 10.1148/radiology.217.2.r00nv24331
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted MR Imaging of the Brain

Abstract: Diffusion-weighted magnetic resonance (MR) imaging provides image contrast that is different from that provided by conventional MR techniques. It is particularly sensitive for detection of acute ischemic stroke and differentiation of acute stroke from other processes that manifest with sudden neurologic deficits. Diffusion-weighted MR imaging also provides adjunctive information for other cerebral diseases including neoplasms, intracranial infections, traumatic brain injury, and demyelinating processes. Becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
612
3
30

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 960 publications
(662 citation statements)
references
References 90 publications
17
612
3
30
Order By: Relevance
“…Several studies on the application of this technique to other regions such as the brain, spinal cord, and breast reported that the usefulness of this technique was limited and inferior to that of EPI 5,24,25 . Kito et al 13 , however, reported that many kinds of tissues in the oral and maxillofacial regions were relatively well visualized in all subjects on FASE DWI (HASTE DWI), but not well on EPI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies on the application of this technique to other regions such as the brain, spinal cord, and breast reported that the usefulness of this technique was limited and inferior to that of EPI 5,24,25 . Kito et al 13 , however, reported that many kinds of tissues in the oral and maxillofacial regions were relatively well visualized in all subjects on FASE DWI (HASTE DWI), but not well on EPI.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI) allows visualization of microscopic water diffusion in biological tissues [2][3][4][5] , and has been applied to head and neck lesions. Many researchers have applied echo-planar imaging (EPI) to DWI of head and neck lesions, as well as diagnosis of diseases of the central nerve system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A direct mathematical relationship exists between the position of these minima and the average mean diameter of the cells. It has already been shown that the PFGSTE NMR experiment is able to probe RBC shape (12) and, especially, to distinguish discocytes and spherocytes from their respective characteristic qspace plots; to characterize CNS structure (13)(14)(15)(16) and to study their pathologies (17)(18)(19).…”
mentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI) of MRI is a recently prevailing technique used to show tissue characteristics based on tissue-specific diffusion motion of water molecules (6,7). Normal endometrium has a high DWI signal intensity because of its high cellularity and abundant cytoplasm (8).…”
mentioning
confidence: 99%